Comparability of the crime surveys in the UK: a comparison of victimisation and technical details - Norris, Paul (Report, 2010)
The ability to compare crime rates using recorded offences is limited because crimes are defined and recorded in different ways across the different jurisdictions within the UK. Crime surveys offer a more standardised approach to comparing crime rates and trends. The population of the UK is covered by three separate crime surveys; the British Crime Survey (BCS) which covers England and Wales; the Scottish Crime Survey (SCS) and the Northern Ireland Crime Survey (NICS). The geographic coverage of these surveys reflects the three jurisdictions within the UK. This paper aims to map differences between the BCS, SCS and NICS which may influence the estimates of victimisation. Although this paper concentrates on victimisation rates the analysis presented could be expanded to other substantive areas, for example fear of crime or perceptions of the criminal justice system. This paper is based primarily on an analysis of information contained in the published technical reports for each survey. To that extent we have been limited by how the ranges of topic covered, and level of detail given, varied between technical reports. While these differences do not directly affect the comparability of the different surveys, they limit researchers’ ability to conduct comparative research because it is not immediately apparent the extent to which the surveys may vary in terms of methodology and content. The issues covered in this paper can be grouped into three broad categories: The sample: who and how many people are asked?; The questions: what are people asked about? Are they asked in the same way?; Coding: how are the answers people provide turned into data?